Performance, nutrient digestibility, and quantitative carcass traits of lambs fed sunflower seeds and Vitamin E - De Almeida, Fabiana Alves [UNESP]; Sobrinho, Américo Garcia Da Silva [UNESP]; Manzi, Gabriela Milani; Lima, Natália Ludmila Lins; Sales, Ronaldo Oliveira; Zeola, Nivea Maria Brancacci Lopes [UNESP]; Endo, Viviane [UNESP]; Borghi, Thiago Henrique [UNESP] (Universidade Estadual de Londrina, 2016)
The aim of this study was to evaluate performance, nutrient digestibility, and carcass quantitative traits of lambs fed diets with and without sunflower seeds and Vitamin E. Thirty-two uncastrated lambs at approximately 60 days of age, with 15 ± 0.2 kg, were housed in individual stalls and slaughtered at 32.0 ± 0.2 kg body weight. Treatments consisted of the following four diets: C = sugarcane + concentrate; CS = sugarcane + concentrate with sunflower seeds; CE = sugarcane + concentrate with 1,000 mg Vitamin E kg-1 diet dry matter (DM); and CSE = sugarcane + concentrate with sunflower seeds and 1,000 mg Vitamin E kg-1 diet DM. The experimental design was completely randomized, in a 2 × 2 factorial arrangement (with and without sunflower seeds and with or without Vitamin E, on the diet DM basis), and means were compared by Tukey's test at 5% significance level. Consumption of Vitamin E intake by the lambs provided (P<0.05) the highest ether extract intake (20.91 g day-1) and consequently the highest (P<0.05) digestibility of this nutrient (85.34%); however, it reduced (P<0.05) the intakes of total carbohydrates (394.81 g day-1) and non-fibrous carbohydrates (242.47 g day-1) as a direct consequence of the diet composition. Inclusion of sunflower seeds and Vitamin E in the lamb diets did not influence (P>0.05) carcass morphological or quantitative measurements. Sunflower seeds and Vitamin E showed to be satisfactory alternatives for inclusion in the concentrate for feedlot lambs, providing good performance and quality carcasses.
Keywords: Antioxidant; Commercial cuts; Oilseeds; Sheep